Teaching Through Polemical Spaces at a Florida Public University: Against the backdrop of Florida state politics and attempts to ban CRT and DEI from higher education settings, the authors embedded an intense reflection component and an assessment to gauge the efficacy and perceived educational value of a trip to the Legacy Museum and the National Memorial for Peace and Justice. - Evans, Jocelyn; Tomso, Gregory; Owusu-Daaku, Kwame (Experiential Learning and Teaching in Higher Education, 2023)
Every year, the University of West Florida Kugelman Honors Program takes a day trip to Montgomery, AL, to visit the Legacy Museum and the National Memorial for Peace and Justice. As a program, we invest heavily in this experience to get students outside of the classroom and grapple with difficult histories that inform our regional and national communities today. Against the backdrop of Florida state politics and attempts to ban CRT and DEI from higher education settings, we embedded an intense reflection component and an assessment to gauge the efficacy and perceived value of the trip from a pedagogical perspective. Here, we provide background on the experience, review the scholarship on critical reflection in applied learning, review the research design, and present the results of the analysis.